Lack of Clinically Meaningful Effect of Cariprazine on the Pharmacokinetics of a Combined Oral Contraceptive - Márta Erzsébet Rosa; Zoltán Juhász; Gabriella Pásztor Mészáros; Gabriella Magyar; Judit Harsányi; Balázs Szatmári; Zoltán Hujber; Máté Szabó; Margit Kapás (Neurology and Therapy)
Abstract Introduction Cariprazine (CAR) is a potent dopamine receptor partial agonist antipsychotic approved by the EMA and the FDA. To address the uncertainty regarding the effectiveness of hormonal contraceptives during CAR co-administration and whether a second barrier method is necessary, a drug–drug interaction study with an oral contraceptive was conducted post-approval. Methods The phase I, fixed-sequence multicenter study involved two periods with 24 patients with schizophrenia, aiming to evaluate the effect of CAR on the pharmacokinetics (PK) of a combined oral contraceptive (COC) containing 30 μg ethinylestradiol (EE) and 150 μg levonorgestrel (LNG). In period A, a single dose of COC alone was administered on day 1. In period B, the highest therapeutic dose of 6 mg CAR was administered once daily from day 4, and a second dose of COC was given concomitantly on day 31. Results Overall, CAR had no clinically meaningful effect on the PK of the COC. The terminal half-life and the time of maximum plasma concentration of EE and LNG were not altered by CAR co-administration. The highest difference observed was a decrease of 14% in the maximum plasma concentration of EE, with only slight deviation of the 90% confidence interval (CI) of the test/reference ratio (77.09–96.81) from the generally accepted bioequivalence range of 80–125%, which is not considered clinically relevant. Confidence intervals of all other exposure measures were within the 80–125% range for both EE and LNG. Conclusions According to these results, hormonal contraceptives can be considered effective during CAR treatment. Trial Registration Trial registration number (EudraCT) 2018-003722-80.